Unleashing the potential of blended learning: An in-depth investigation in Indonesia and Malaysia - Saputra, Setiya Yunus; Muzakki, Abdurrohman; Abdullah, Khairul Hafezad; Demir, Gonul Tekkursun; Setiawan, Edi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
A limited literature on mixed method research to reveal the effect of blended learning in physical education turn out to be a gap in this research. Therefore, our study aims to investigate the perceptions of teachers about the effects, effectiveness, and challenges of blended learning in physical education classes through mixed-methods research. This study adopted a mixed-methods type with a mixed methods research. There were 12 participants involved in this study, which included elementary school teachers (n=4) and high school teachers (n=4) from Indonesia and elementary school teachers (n=2) and high school teachers (n=2) from Malaysia. The qualitative instrument included in-depth interviews. While, the quantitative instrument used a questionnaire. The qualitative study used statistical analysis with qualitative thematic methods. Meanwhile, in the quantitative study, all responses from 12 analyses were to find the frequency and percentage values of each response. Based on the results of the qualitative study, the majority of teachers perceived that blended learning in physical education classes had a significant effect on the development of students' domains and it was effective to implement physical education learning in elementary schools and high schools. While, results of quantitative study show that the biggest challenges due to the implementation of blended learning in physical education were the lack of technological facilities (86.2%), lack of understanding of teachers and students (72.7%), poor internet connection (64.8%), and limited learning duration in offline classes (50.0%). Therefore, the results of this study are essential and must be evaluated continuously, so that the physical education learning process through blended learning in a sustainable manner can have a positive effect on students at all levels of education in Indonesia and Malaysia or other countries in the world.